Attention, social representation and vocal communication in the European starling (Stumus vulgaris) and the African pale-winged starling (Onychognathus nabouroup) - (:unkn) unknown (My University, 2022)
In this thesis, we investigated social cognition in two songbird species, the European starling (Sturnus vulgaris) and the pale-winged starling (Onychognathus nabouroup). Social cognition refers to abilities such as perception, categorisation or memory that allow animals to organise their interactions with other animals. These abilities are essential for individuals as they allow them to be aware to their social and non-social environment and thus to choose a sexual partner, to interact with other animals (conspecific and heterospecific) and to communicate. In a first step, we investigated the effect and time effect on individual attentional characteristics in starlings living in two different living conditions (captive in naturalistic conditions, captive in impoverished conditions). Furthermore, we characterised the potential relationship between these attentional characteristics and vocal communication. To do this, we recorded the starlings' vocal communication individually and then characterised their visual attention through standardised attention tests. The type of stimuli were visual or auditory, social or non-social. We showed that regardless of their living conditions, individuals, in response to stimuli, produced more glances (< 1s) than gazes (> 1s) and used their monocular vision more than their binocular vision. Animals reared under impoverished conditions produced more attentional behaviours than individuals reared under naturalistic conditions. We also showed that some of the attention behaviour observed between and within groups changed with the duration of exposure of the birds to their respective living conditions. Others, on the contrary, remained stable. Finally, it appeared that starlings reared in naturalistic conditions sang more often than those living in impoverished conditions and that starlings with a developed social network were also the most attentive. In a second phase, we developed a new and original method
Keywords: African Research